Manufacturing mastery : the path to building successful and enduring manufacturing businesses - Morgan, Rebecca (Productivity Press, 2021)
While there are those who say manufacturing is dying, it is not and will not. Without a universal vow of poverty, growing economies will only increase demand. Manufacturing in the 21st century is not a question of if -- Rather, it is a function of why, what, who, where, and how. The nature and pace of change in those factors are overwhelming many. Fear, futile resistance, and uncertainty are common. While manufacturing will not die, individual manufacturing companies will if they do not learn to thrive in this new world. This book is a dynamic guide for manufacturing leaders who want to reduce the ambiguity and overwhelming changes and develop a realistic, progressive, and responsive thinking process that enables success. It provides a business operating system framework that is the foundation for connecting the many pieces of a manufacturing business into an effective, profitable operation. The author walks through the elements, relationships, capabilities, and mutability 21st-century manufacturing requires. Executives of manufacturing companies will be better able to think about and execute viable strategies leveraging the changing economy. Essentially, manufacturing is becoming increasingly complex, as are business and socioeconomic and political realities. Rapidly evolving technology adds to the confusing environment that precludes more of the same, better, faster and cheaper as a workable business strategy. The tsunami of information hitting owners and leaders is overwhelming many, and it is easy to become frozen in place. Economic growth and improving standards of living require that all of this change be broken into bite-size understandable pieces that thaw the minds of executives, allowing them to assess what is best right now, and move forward. This book does not overwhelm with details and models; rather it provides thinking and examples in small chunks that enable manufacturers to develop and master skills for high-level strategic leadership in ambiguity.